Increased Serum Levels of Soluble TNF-α Receptor Is Associated With ICU Mortality in COVID-19 Patients - Mortaz, Esmaeil; Tabarsi, Payam; Jamaati, Hamidreza; Dalil Roofchayee, Neda; Dezfuli, Neda K.; Hashemian, Seyed MohammadReza; Moniri, Afshin; Marjani, Majid; Malekmohammad, Majid; Mansouri, Davood; Varahram, Mohammad; Folkerts, Gert; et al. (Frontiers in Immunology, 2021)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) has infected over 112M patients and resulted in almost 2.5M deaths worldwide. The major clinical feature of severe COVID-19 patients requiring ventilation is acute respiratory distress syndrome (ARDS) possibly associated with a cytokine storm. Objectives To elucidate serum levels of TNF-α and soluble TNF-Receptor 1 (sTNFR1) in patients with severe and mild COVID-19 disease as determinants of disease severity. Methods We determined serum TNF-α and sTNFR1 concentrations in 46 patients with laboratory-confirmed COVID-19 (17 patients with severe disease within the intensive care unit [ICU] and 29 non-severe, non-ICU patients) and 15 healthy controls upon admission using ELISA. Subjects were recruited between March-May 2020 at the Masih Daneshvari Hospital Tehran, Iran. Results Serum levels of sTNFRI were significantly higher in ICU patients (P<0.0001) and non-ICU patients (P=0.0342) compared with healthy subjects. Serum sTNFR1 were significantly higher in ICU patients than in non-ICU patients (P<0.0001). Serum TNF-α levels were greater in ICU and non-ICU patients than in the healthy subjects group (p<0.0001). The sTNFRI concentration in ICU (r=0.79, p=0.0002) and non-ICU (r=0.42, p=0.02) patients positively correlated with age although serum sTNFRI levels in ICU patients were significantly higher than in older healthy subjects. The sTNFRI concentration in ICU patients negatively correlated with ESR. Conclusions The study demonstrates higher sTNFRI in ICU patients with severe COVID-19 disease and this be a biomarker of disease severity and mortality. Future studies should examine whether lower levels of systemic sTNFR1 at admission may indicate a better disease outcome.